"Moving on to an Open World": A Study of Participants' Experience in Meaningful Activities and Recovery (MA&R) - Nanna Kaas Tepavicharov; Jeanette Reffstrup Christensen; Tom Møller; Lene Falgaard Eplov; Siv Therese Bogevik Bjørkedal (Hindawi-Wiley, 2022)
Background. Meaningful activities and Recovery (MA&R) is a peer coled occupational therapy intervention, to support occupational engagement among persons with psychiatric disabilities. Aim. To investigate participants' perspectives on how MA&R influenced occupational engagement and recovery processes. Material and Methods. A qualitative study with a phenomenological-hermeneutic design. Individual semistructured interviews were conducted with three women and ten men who had participated in MA&R. Participants were recruited from community mental health centres and municipality mental health services in two Danish municipalities. Analysis strategy was based on Malterud's Systematic Text Condensation. Results. MA&R was perceived as a practical approach to recovery, by providing an opportunity for reorientation, meaning, making in mundane activities, and a new outlook on everyday life. Participating in MA&R challenged a black and white approach to activities, put emphasis on "the little things", and enhanced curiosity, presence, and joy in occupational engagement. Conclusion. MA&R supported participants in developing a new "lens" on meaningful activities. The lens enhanced occupational engagement and made it possible to live according to personal preference. Results can inform further development and delivery of recovery-oriented occupational therapy interventions and add to the understandings of how occupational engagement and recovery are intertwined and manifested through everyday experiences. Thus, occupational engagement is an important target for recovery-oriented interventions. Occupational therapists and peer-workers coleading such interventions is feasible and makes good sense to the participants.